OUTDOOR EDUCATION AND GEOGRAPHICAL EDUCATION - ANDREA GUARAN (Romanian Review of Geographical Education, 2016)

(untitled)
This paper focuses on the reflection on the relationship between values and methodological principles of Outdoor Education and spatial and geographical education perspectives, especially in pre-school and primary school, which relates to the age between 3 and 10 years. Outdoor Education is an educational practice that is already rooted in the philosophical thought of the 16th and the 17th centuries, from John Locke to Jean-Jacques Rousseau, and in the pedagogical thought, in particular Friedrich Fröbel, and it has now a quite stable tradition in Northern Europe countries. In Italy, however, there are still few experiences and they usually do not have a systematic and structural modality, but rather a temporarily and experimentally outdoor organization. In the first part, this paper focuses on the reasons that justify a particular attention to educational paths that favour outdoors activities, providing also a definition of outdoor education and highlighting its values. It is also essential to understand that educational programs in open spaces, such as a forest or simply the schoolyard, surely offers the possibility to learn geographical situations. Therefore, the question that arises is how to finalize the best stimulus that the spatial location guarantees for the acquisition of knowledge, skills and abilities about space and geography.